Thermo-magnetic convection of nanofluid in a triangular cavity with a heated inverted triangular object. (2022) - Chatterjee, Deep; Manna, Nirmal K.; Biswas, Nirmalendu
Abstract: The present study aims to explore the buoyancy-driven convective phenomena of nanofluid flow in a cavity of an isosceles triangle with an inverted triangular heat source under the effect of a sloped magnetic field. The cases of different heating loads are analyzed considering various sizes of the heating triangle. The outer triangular cavity is kept at a lower temperature; whereas the inner inverted triangular is maintained as the isothermal heat source. Space in-between the inner and other triangle is filled with nanofluid (Al2 O3 -water). Finite element methodology is adapted to compute the coupled transport equations numerically. The convective phenomena and associated heat transfer characteristics are examined systematically for a range of control parameters like Rayleigh numbers (10 3 –10 6 ), Hartmann number (0–70), and magnetic field inclination angle (0−180°), and the size of the inner inverted triangular heat source. The illustrations of local distribution of streamlines, isotherms, entropy generation are presented along with the average Nusselt number, Nu. It shows that the size of the inner triangular heat source controls the overall thermal behavior. The maximum convective heat transfer is obtained with the least flow obstruction (i.e. smaller size of the inner triangle). The study of magnetic field inclination shows that maximum heat transfer is obtained at an inclination of 90° and minimum flow obstruction.